Derivation of Phase 3 dosing for peginterferon lambda‐1a in chronic hepatitis C, Part 2: Exposure–response analyses for efficacy and safety variables. (24th July 2014) - Hruska, Matthew; Wang, Xiaodong; Chan, Phyllis; Ahmad, Alaa; Freeman, Jeremy; Horga, Maria Arantxa; Hillson, Jan; Kansra, Vikram; Lopez‐Talavera, Juan‐Carlos
Abstract This is the second of two manuscripts detailing the pharmacodynamic derivation of peginterferon lambda‐1a (Lambda) dosing and treatment durations for Phase 3 studies in hepatitis C virus (HCV) infection, based on Phase 2 data. Herein, we describe the derivation of regression models for 12‐week on‐treatment virologic response and safety outcomes at 120, 180, and 240 μg Lambda with ribavirin. In patients with HCV genotypes 1 or 4, there was a significant (P = 0.024) relationship between undetectable HCV‐RNA at Week 4 and Lambda exposure (AUC or Cmax), with the largest difference between adjacent dose levels between the 180 and 120 μg exposure ranges. Risk of Grade 3–4 aminotransferase or bilirubin elevations relative to a peginterferon alfa‐2a/ribavirin control were related to Lambda exposure for all patients, and the largest increase between adjacent dose levels was seen for 240 versus 180 μg. Anemia and neutropenia events were lower than control across all doses and exposures. Based on these data and those in our previous manuscript, Phase 3 studies will evaluate fixed 180 µg doses of Lambda in combination with ribavirin and a direct‐acting antiviral for 24–48 weeks in HCV genotypes 1 or 4 or 12–24 weeks in genotypes 2 or 3.